Aproveitamento da borra de café para produção de lipases por fungos filamentosos isolados do Rio Igarassu, PE, Brasil. - França, Eduardo da Silva (2021)
The production of microbial enzymes has increased in recent decades, due to its enormous versatility in several industrial processes. Lipases (EC 3.1.1.3) are hydrolases that catalyze the conversion of triacylglycerols to free fatty acids and glycerol. These enzymes are produced by several filamentous fungi, yeasts, and bacteria. In this work, the bioconversion of spent coffee grounds into lipases by filamentous fungi isolated from water of the Igarassu River, located in the city of Igarassu in the State of Pernambuco, Brazil, was investigated. Therefore, water samples were collected and processed for the isolation of filamentous fungi. Then, the filamentous fungi were morphologically identified and submitted to a preliminary test in solid state fermentation, with 10 g of spent coffee grounds, 60% moisture at a temperature of 28 °C for 144 h to select the fungus with the greatest potential for production of lipases. By using a 23 full factorial design, the main effects and interactions of the moisture (%), temperature (°C) and spent coffee grounds concentration (g) were evaluated in the production of lipase by the selected fungus. Five filamentous fungi were isolated and identified: Aspergillus flavus UCP 0316, Aspergillus fumigatus UCP 0327, Paecillomyces variotii, UCP 0334, Mucor hiemalis f. luteus UCP 0343 e Aspergillus foetidus UCP 0360. All 5 filamentous fungi were able to grow and produce lipases in spent coffee grounds, however, a higher production was observed in Aspergillus species, with emphasis on A. foetidus UCP (0327) which exhibited an enzymatic activity of 514.29 U/mL. The highest lipase production of 2941.87 U/ml was obtained when A. foetidus UCP 0360 was cultivated in 25 g of spent coffee grounds, 37 °C and 50% moisture for 144 h in solid state fermentation. Therefore, we emphasize that spent coffee grounds are a promising agro-industrial residue to produce lipases, contributing to the reduction of environmental pollution and generating value-added products for the industry.